Pengaruh Struktur Kepemilikan, Karakteristik Dewan, dan Kesulitan Finansial terhadap Penghindaran Pajak - Kennardi Tanujaya; Dewi Ratna; Iwan Suhardjo (Faculty of Economics, Universitas Internasional Batam, 2021)
This study examines whether variations in ownership structure, board characteristics, and financial distress have an impact on the level of tax avoidance in Indonesia. Independent variables included in the study are family ownership, institutional ownership, managerial ownership, foreign ownership, the composition of the board of commissioners, the independence of the board of commissioners, the frequency of board meetings, and financial distress. Effective tax rate (ETR) and cash flow effective tax rate (CFETR) act as a measurement to determine the dependent variable namely tax avoidance. Control variables are firm size, profitability, leverage, and market to book value. This study is designed as a causal-comparative study in which the relationship of each variable is tested. The population consists of all companies listed on the IDX in the 2014-2018 period. Listed companies are classified based on specified criteria to obtain observations of 460 data for ETR and 506 data for CFETR. The data are processed to form hypotheses using descriptive methods and regression methods. The research concludes that managerial ownership, the composition of the board of commissioners and financial distress negatively affect tax avoidance. While family ownership, institutional ownership, foreign ownership, independence of the board of commissioners and the frequency of board meetings do not have a significant relationship to the practice of tax avoidance.